Verification of an Optimal Adaptive Filtering Algorithm for GNSS Antenna Arrays. Issue 4 (30th January 2017) - Buchanan, Matthew; Chuang, Ying Chieh; O'brien, Andrew J.; Gupta, Inder J.
Abstract: This paper presents experimental verification of an optimal adaptive filtering algorithm with zero antenna‐induced biases for Global Navigation Satellite Systems adaptive antenna arrays utilizing Space Time Adaptive Processing. GPS L1 C/A‐coded signals and unencrypted P‐coded signals for multiple satellites were generated by a signal generator and transmitted inside an anechoic chamber along with strong narrowband and wideband interferers. The signals received by a six‐element antenna were digitized and recorded for multiple interference scenarios and post‐processed using antenna electronics and a GPS receiver implemented in software. The delay and carrier phase measurements made by the receiver for different interference scenarios using the optimal adaptive algorithm are compared to a reference solution to examine the antenna‐induced biases of the algorithms. The results show that the optimal adaptive algorithm successfully prevented the array from introducing significant bias errors, even in the presence of harsh interference. Modifications and improvements to the original algorithm are also discussed. Copyright © 2017 Institute of Navigation